A microfluidic platform for functional testing of cancer drugs on intact tumor slices. Issue 9 (9th April 2020) - Rodriguez, A. D.; Horowitz, L. F.; Castro, K.; Kenerson, H.; Bhattacharjee, N.; Gandhe, G.; Raman, A.; Monnat, R. J.; Yeung, R.; Rostomily, R. C.; Folch, A.
Abstract : We have developed a digitally-manufacturable microfluidic platform that allows for multiplexed drug testing of intact tumor slices. Abstract : Present approaches to assess cancer treatments are often inaccurate, costly, and/or cumbersome. Functional testing platforms that use live tumor cells are a promising tool both for drug development and for identifying the optimal therapy for a given patient, i.e. precision oncology. However, current methods that utilize patient-derived cells from dissociated tissue typically lack the microenvironment of the tumor tissue and/or cannot inform on a timescale rapid enough to guide decisions for patient-specific therapy. We have developed a microfluidic platform that allows for multiplexed drug testing of intact tumor slices cultured on a porous membrane. The device is digitally-manufactured in a biocompatible thermoplastic by laser-cutting and solvent bonding. Here we describe the fabrication process in detail, we characterize the fluidic performance of the device, and demonstrate on-device drug-response testing with tumor slices from xenografts and from a patient colorectal tumor.